Frontostriatal Structural Connectivity and Striatal Glutamatergic Levels in Treatment-Resistant Schizophrenia: An Integrative Analysis of DTI and 1H-MRS. Issue 1 (26th October 2020) - Ochi, Ryo; Tarumi, Ryosuke; Noda, Yoshihiro; Tsugawa, Sakiko; Plitman, Eric; Wada, Masataka; Honda, Shiori; Matsushita, Karin; Chakravarty, M Mallar; Graff Guerrero, Ariel; Fujii, Shinya; Matsui, Mie; et al.
Abstract: Given that approximately one-third of patients with schizophrenia do not respond to antipsychotics, different neurobiological bases may underlie treatment resistance in schizophrenia. Previous studies showed that treatment response is associated with both frontostriatal connectivity and glutamatergic neurometabolite levels in the caudate in patients with schizophrenia, which leads to the hypothesis that the relationship between them may be altered, specifically in patients with treatment-resistant schizophrenia (TRS). Employing analyses of covariance and subsequent partial correlation analyses, we compared the relationship between glutamate+glutamine (Glx) levels in the caudate and fractional anisotropy (FA) values in the tract between the dorsolateral prefrontal cortex and caudate in 19 patients with TRS, 20 patients responsive to first-line antipsychotics (FL-Resp), and 19 healthy controls (HCs). TRS was defined by severe positive symptomatology despite first-line antipsychotic treatment. Patients with TRS had lower FA values in the bilateral frontostriatal tracts than patients with FL-Resp and HCs ( P < .001), while no group differences were found in caudate Glx levels. There was a significant frontostriatal FA value-by-group interaction on caudate Glx levels ( F = 7.37, P = .009). Frontostriatal FA values positively correlated with caudate Glx levels in HCs ( r = −.55, P = .028), while they were negatively associated with caudate Glx levels in the TRS group ( r = .53, P = .043). Furthermore, in the FL-Resp group, frontostriatal FA values did not significantly correlated with caudate Glx levels. The altered relationship between white matter integrity and the glutamate system in the frontostriatal circuit in the TRS group may reflect the pathophysiology underlying treatment response/resistance in schizophrenia.